Pengaruh Desain Produk, Kualitas Produk Dan Brand Awareness Terhadap Keputusan Pembelian Produk Starbucks Grand Batam Mall - Windy; Suhardi (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2024)
Research on the influence of product design, product quality and brand awareness on purchasing decisions for Grand Batam Mall Starbuck’s product is an experiment based on the researcher’s  experience and other Starbucks consumers which refers to the influence of design, quality and brand awareness of Starbucks products. This research aims to describe the influence of product design, product quality, and product brand awareness on a decision to purchase Starbuck’s product. This research uses quantitative research methods with the treatment of determining the population and samples that will be collected through distributing questionnaires. There is a total sample of 100 using the Lemeshow formula and it is determined that product design has a positive influence on buyer decisions (t count 2.927 > t table 1.985 and Sig. 0.004 < 0.05), product quality has a positive influence on buyer decisions (t count 4.675 > t table 1.985 and Sig. 0.000 < 0.05), and brand awareness has a positive influence on buyer decisions (t count 3.719 > t table 1.985 and Sig. 0.002 < 0.05). So it can be concluded that the design, quality and brand awareness of the product really influence the decision results of Grand Batam Mall Starbucks consumers.